Preference segments in beef purchase - Groot, Etiénne [UNESP] (FapUNIFESP (SciELO), 2021)
The objective of this work was to investigate the consumer preferences of the main attributes involved on beef purchase process, in Dracena-Sao Paulo State, Brazil. Thus, it was carried out 116 interviews in the city's public thoroughfares, in July and August 2017. A structured questionnaire was used for interviews. Average preferences were determined by multinomial logistic regression and market segments were estimated through the latent class analysis. Results show that the most important attribute of beef purchase process is its appearance and it is followed by the expiration data on the packaging and meat freshness. It was found that there are five market segments. The largest, which comprises 31.3% of consumers, is characterized by the importance given to those attributes related to organoleptic quality. The second segment represents the preference of 18.9% of consumers, and they were defined as concerned with health, for giving priority to beef's smell and freshness. The smallest segment is only 8.6% of consumers. To increase beef acceptance, it is necessary to take care of its aspect at selling point, and it must be in a good conservation state and with a recent slaughter date.
Segmentos de preferências na aquisição da carne bovina
Keywords: Attribute; Consumer behavior; Discrete choice experiment; Latent class